2015
DOI: 10.2174/2211536604666150813152450
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and Physical Activity

Abstract: Micro-RNAs (miRNAs) are responsible for important and evolutionary-conserved regulatory functions in several cellular processes such as apoptosis, signalling, differentiation and proliferation. There is a growing interest in understanding more clearly the mechanisms regulating activation and suppression of miRNAs expression in benefit of health prevention advancement. It is now acknowledged that physical activity represents one of the most effective preventive agents in chronic degenerative diseases. Indeed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 125 publications
0
16
0
Order By: Relevance
“…miRNAs are able to negatively modulate gene expression via direct interactions with the 3'-untranslated regions (3'-UTRs) of their target genes in an imperfect or perfect base pairing manner, and therefore, inducing translational suppression and/or mRNA degradation (11). Consequently, miRNAs are implicated in the regulation of a series of biological behaviors, including cell proliferation, differentiation, metabolism and carcinogenesis (12). Emerging data have revealed that miRNAs are abnormally expressed in almost every type of human cancer, including NSCLC (13), cervical cancer (14), colorectal cancer (15), prostate cancer (16) and breast cancer (17).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are able to negatively modulate gene expression via direct interactions with the 3'-untranslated regions (3'-UTRs) of their target genes in an imperfect or perfect base pairing manner, and therefore, inducing translational suppression and/or mRNA degradation (11). Consequently, miRNAs are implicated in the regulation of a series of biological behaviors, including cell proliferation, differentiation, metabolism and carcinogenesis (12). Emerging data have revealed that miRNAs are abnormally expressed in almost every type of human cancer, including NSCLC (13), cervical cancer (14), colorectal cancer (15), prostate cancer (16) and breast cancer (17).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a selective miRNA export system, it can be speculated that angiogenic miRNAs are released from endothelial cells into the circulation in response to hypoxia or shear stress, too. Recent reviews by Xu et al and Altana et al also consider damaged or apoptotic cells, caused by exercise, as possible sources of c-miRNAs (Altana et al, 2015; Xu et al, 2015). It has been shown that lymphocyte apoptosis occurs in a similar time course as miRNA release (Mooren et al, 2004), underlining that miRNAs could be released from apoptotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…These miRNAs—also called “angiomiR”—are highly expressed in endothelial cells, and have been shown to be regulated by exercise (Suárez and Sessa, 2009 ; Quintavalle et al, 2011 ; Fernandes et al, 2012 ). Recent reviews by Xu et al ( 2015 ) and Altana et al ( 2015 ) summarize numerous studies examining the response of (circulating) miRNAs to exercise. For circulating miRNA-126, the maximum expression level was determined during endurance exercise 30 min after the start (Uhlemann et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fernandes et al ( 2012 ) have analyzed the expression of miR-16, -21, and -126 in muscles after exercise and reported an up-regulation of miR-21 and miR-126. However, researchers have yet to determine if circulating miRNAs change in children in response to exercise and if the molecular response is affected by different training protocols (Altana et al, 2015 ; Xu et al, 2015 ). HIIT or HVT, are well-known stimuli with positive effects on endothelial function and angiogenic processes (Egginton, 2009 ).…”
Section: Introductionmentioning
confidence: 99%